If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9d + d + -1d + 2 + -3d = 0 Reorder the terms: 2 + 9d + d + -1d + -3d = 0 Combine like terms: 9d + d = 10d 2 + 10d + -1d + -3d = 0 Combine like terms: 10d + -1d = 9d 2 + 9d + -3d = 0 Combine like terms: 9d + -3d = 6d 2 + 6d = 0 Solving 2 + 6d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6d = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 6d = 0 + -2 6d = 0 + -2 Combine like terms: 0 + -2 = -2 6d = -2 Divide each side by '6'. d = -0.3333333333 Simplifying d = -0.3333333333
| 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 | | 3(x+2)=2(x+1)-5 | | 8y-6=4y-18 | | 3a+22=7a+14 | | 2n-8=6n-32 | | 2(2x+6)=5x+9 | | 16x+27=75 | | -18=6k+6(1+3k) | | 2n-8=6n-(-32) | | f-14=6f | | 4(x+3)-12=3(x-6) | | 4x^3-12x^2-64x+192=0 |